246 IMPROVING LUMBAR PUNCTURE TECHNIQUE AMONG INTERN TRAINEES TO ENHANCE QUALITY OF CARE FOR PATIENTS. (18th November 2021) - Antonenko, A; Shanahan, E; Slattery, N; Leahy, A; Gabr, A; Condon, J; Ahern, E; O'Connor, M
Abstract: Background: Lumbar puncture (LP) is a common procedure performed on older adults in acute medical settings. A higher peri-procedural risk has been shown in older patients. Non-consultant doctors (NCHDs) often lack confidence and competence in performing LP. Simulation based training using task trainers has been shown to improve confidence, preplanning skills and technique. Methods: A simulation based teaching session was developed in a university teaching hospital (training structure was adapted from the LP training guide published in MedEdPortal). Small group teaching (with 6–8 learners) was delivered to 25 NCHDs with no prior exposure or experience with lumbar puncture completion. Trainees completed one LP simulation without practice to mastery level. On-demand and post-performance feedback was delivered to learners. An assessment checklist was completed by the supervisor. Learners completed an anonymised quantitative and qualitative questionnaire using Qualtrics XM software at a later date to evaluate self-perceived teaching outcomes. Results: 16 doctors completed the questionnaire (64% response rate). 55% rated the LP workshop as a 'strongly positive' impact on their learning, while 18% indicated a 'positive' impact on a 5-point Likert scale. 19% of trainees reported they were 'very comfortable' at performing the procedure post training, with 56.5% 'comfortable' to perform an LP in their clinical practice. Qualitative learner feedback included 'more hands on practice' on the mannequin, 'smaller groups for the workshops' and 'more practice tips' during the simulation workshop. Conclusion: This pilot study demonstrated interest and positive feedback for the LP simulation training from novice doctors with improved self-assessed confidence. Formal development of an LP simulation training curriculum is underway. The impact of this training on patient care should be assessed in practice.